2017
DOI: 10.17140/oroj-4-128
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index is a Strong Predictor of Vitamin D Deficiency in Multiethnic Obese Children

Abstract: CitationKannan S, Visintainer P, Ganguri HB, Conroy R, Gudala M, Wittcopp C. The main objective of this study is to determine predictors of vitamin D deficiency in obese children. Methods: Children aged 5-14 years with body mass index z-score (BMIZ)>95% were enrolled. Data included height, weight, ethnicity, season, dietary intake, serum 25-hydroxy vitamin D test: (25(OH)D), parathyroid hormone, calcium, insulin, glucose, high sensitivity C-reactive protein (CRP), lipids, aspartate aminotransferase (AST), ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…Our univariate analysis showed that vitamin D deficient children showed higher BMI compared to non-deficient (Table 1, Supplementary Figure S6), suggesting that overweight children are at significantly greater risk of vitamin D inadequacy. Additionally, the multivariate regression analysis demonstrated that BMI z scores were inversely related to vitamin D levels; these data were consistent with numerous studies demonstrating that BMI z scores are strong predictors of vitamin D levels, especially in children [114][115][116][117][118][119]. This reduction in the levels of serum 25(OH)D coinciding with an increase in BMI z scores may be due to volumetric dilution of vitamin D in the large adipose stores or excess sequestration of vitamin D in fat, leading to decreased bioavailability [115].…”
Section: Discussionsupporting
confidence: 89%
“…Our univariate analysis showed that vitamin D deficient children showed higher BMI compared to non-deficient (Table 1, Supplementary Figure S6), suggesting that overweight children are at significantly greater risk of vitamin D inadequacy. Additionally, the multivariate regression analysis demonstrated that BMI z scores were inversely related to vitamin D levels; these data were consistent with numerous studies demonstrating that BMI z scores are strong predictors of vitamin D levels, especially in children [114][115][116][117][118][119]. This reduction in the levels of serum 25(OH)D coinciding with an increase in BMI z scores may be due to volumetric dilution of vitamin D in the large adipose stores or excess sequestration of vitamin D in fat, leading to decreased bioavailability [115].…”
Section: Discussionsupporting
confidence: 89%
“…For example, increased use of TV, video or computers [ 37 , 38 , 39 ], less physical activity [ 33 , 38 , 39 , 40 , 41 , 42 , 43 ], low sun exposure [ 33 , 41 , 42 , 43 , 44 ], low levels of milk consumption [ 33 , 37 , 43 , 45 ] and high levels of soft drink consumption [ 45 ] can increase the risk of developing vitamin D deficiency in children aged 1–18 years. At age 6–16 years, children were vitamin D deficient in spring and winter [ 35 , 36 , 39 , 41 , 46 , 47 , 48 ] and girls were found to be more vitamin D deficient than boys [ 33 , 34 , 36 , 37 , 48 , 49 , 50 ]. Low vitamin D status is a significant concern in children aged 3–18 years from some racial/ethnic minorities and urban communities in USA, Central and Western Europe, Southern Asia and Eastern Africa [ 39 , 40 , 41 , 44 , 45 , 47 , 48 , 50 ].…”
Section: Vitamin D In Children: Assessment Of Status and Deficiencmentioning
confidence: 99%
“…At age 6–16 years, children were vitamin D deficient in spring and winter [ 35 , 36 , 39 , 41 , 46 , 47 , 48 ] and girls were found to be more vitamin D deficient than boys [ 33 , 34 , 36 , 37 , 48 , 49 , 50 ]. Low vitamin D status is a significant concern in children aged 3–18 years from some racial/ethnic minorities and urban communities in USA, Central and Western Europe, Southern Asia and Eastern Africa [ 39 , 40 , 41 , 44 , 45 , 47 , 48 , 50 ].…”
Section: Vitamin D In Children: Assessment Of Status and Deficiencmentioning
confidence: 99%
See 1 more Smart Citation
“…Результаты ряда эпидемиологических исследований предполагают связь между дефицитом VD и ожирением у детей и подростков [22][23]. Однако, несмотря на полученные данные, патогенетические механизмы их взаимного влияния остаются изученными не достаточно [24].…”
unclassified